TRP Channels as Targets for Therapeutic Intervention in Obesity: Focus on TRPV1 and TRPM5 - Kyle Palmer, R.; A. Lunn, Charles (Current Topics in Medicinal Chemistry, 2013)
The disease of obesity is one of the greatest healthcare challenges of our time. The increasing urgency for effective treatment is driving an intensive search for new targets for anti-obesity drug discovery. The TRP channel super family represents a class of proteins now recognized to serve many functions in physiology related to maintenance of health and the development of diseases. A few of these might offer new potential for therapeutic intervention in obesity. Among the TRP channels, TRPV1 appears most closely associated with body weight homeostasis through its influence on energy expenditure. TRPM5 has been thoroughly characterized as a critical component of taste signaling and recently has been implicated in insulin release. Because of its role in taste signaling, we argue that drugs designed to modulate TRPM5 could be useful in controlling energy consumption by impacting taste sensory signals. As drug targets for obesity, both TRPV1 and TRPM5 offer the advantage of operating in compartments that could limit drug distribution to the site of action. The potential for other TRP channels as anti-obesity drug targets also is discussed.
Keywords: obesity